The Contribution of the Dorsolateral Prefrontal Cortex in Full and Divided Encoding: A Paired-Pulse Transcranial Magnetic Stimulation Study - Sophie Blanchet; Geneviève Gagnon; Cyril Schneider (Behavioural Neurology)
This research investigated the contribution of the dorsolateral prefrontal cortex (DLPFC) in the attentional resources in episodic encoding for both verbal and non-verbal material. Paired-pulse transcranial magnetic stimulations (TMS) were used to interfere transiently with either the left or right DLPFC during encoding under full attention (FA) or under divided attention (DA) in a recognition paradigm using words and random shapes. Participants recognized fewer items after TMS over the left DLPFC than over the right DLPFC during FA encoding. However, TMS over the left DLPFC did not impair performance when compared to sham condition. Conversely, participants produced fewer items after TMS over the right DLPFC in DA encoding compared to sham condition, but not compared to TMS over the left DLPFC. These effects were found for both words and random shapes. These results suggest that the right DLPFC play an important role in successful encoding with a concomitant task regardless of the type of material.